FEEDING, LOCOMOTOR AND RESTING BEHAVIOR IN MALE CAPTIVE SAMBAR : A SEASONAL STUDY - KAR, A.; DULKAR, R.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1993)
Annual changes in feeding, locomotor and resting activities was studied in captive sambar at Indore (Lat. 22.5 and 76°E). A significant variation in all three activities was noted. Maximum locomotion and feeding activities were observed in the month of September. In contrast, during this month animal showed minimum resting activites. While lowest locomotion was observed in April, feeding was minimum in February. Findings emphasize that moderate environmental conditions are required for the maximum activity in sambar.